2017
DOI: 10.1007/s10151-017-1687-8
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with a dual-console robotic-assisted platform for training in colorectal surgery

Abstract: The DaVinci Xi dual-console platform is a safe and effective platform for training junior surgeons. The dual-console system has the potential to alter surgical training pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The traditional surgical teaching model adopted for open surgery can be reviewed for robotic surgery in ''see one, do side by side one, teach one.'' This approach has already been investigated and validated in different abdominal surgeries and specialties [9,25,26]. These studies demonstrated that the dual-console robotic system could overcome defects of laparoscopic surgical training.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The traditional surgical teaching model adopted for open surgery can be reviewed for robotic surgery in ''see one, do side by side one, teach one.'' This approach has already been investigated and validated in different abdominal surgeries and specialties [9,25,26]. These studies demonstrated that the dual-console robotic system could overcome defects of laparoscopic surgical training.…”
Section: Discussionmentioning
confidence: 96%
“…This approach has already been investigated and validated in different abdominal surgeries and specialties [ 9 , 25 , 26 ]. These studies demonstrated that the dual-console robotic system could overcome defects of laparoscopic surgical training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, Bolger reported that the dual console was a safe and effective platform for training junior surgeons in colorectal surgery, and suggested that the dual console system has the potential to alter surgical training pathways. 13 However, these previous reports did not indicate how many surgeries should be performed with the dual console system in order to instruct to junior surgeons. In our current series, the learning curve reached a plateau after 14 cases.…”
Section: Discussionmentioning
confidence: 98%
“…An another advantage of robotic surgery using the Da Vinci system is that it has a dual console, which several studies have reported is useful as an educational tool for young surgeons. [11][12][13] The dual consoles allow the mentor to instruct the appropriate dissection site with a pointer on the surgeon's monitor, and when the operation is difficult or safety is compromised, the operator can switch the surgeon to a supervising physician in any given moment using the swap mode, and without the need to change seats. Given these advantages, nextgeneration surgeons can start robotic surgery with increased safety and confidence, and as a result, the surgeons may acquire the necessary skills faster than the first generation surgeons, even if they are not proficient to laparoscopic rectal cancer surgery.…”
mentioning
confidence: 99%